Comprehensive evaluation of formulation factors for ocular penetration of fluoroquinolones in rabbits using cassette dosing technique - Sharma C; Biswas NR; Ojha S; Velpandian T (Dove Medical Press, 2016)
Charu Sharma,1,2 Nihar R Biswas,1 Shreesh Ojha,3 Thirumurthy Velpandian1 1Department of Ocular Pharmacology and Pharmacy, All India Institute of Medical Sciences, New Delhi, India; 2Department of Internal Medicine, 3Department of Pharmacology and Therapeutics, College of Medicine and Health Sciences, United Arab Emirates University, Al Ain, UAE Objective: Corneal permeability of drugs is an important factor used to assess the efficacy of topical preparations. Transcorneal penetration of drugs from aqueous formulation is governed by various physiological, physiochemical, and formulation factors. In the present study, we investigated the effect of formulation factors like concentration, pH, and volume of instillation across the cornea using cassette dosing technique for ophthalmic fluoroquinolones (FQs). Materials and methods: Sterile cocktail formulations were prepared using four congeneric ophthalmic FQs (ofloxacin, sparfloxacin, pefloxacin mesylate, and gatifloxacin) at concentrations of 0.025%, 0.5%, and 0.1%. Each formulation was adjusted to different pH ranges (4.5, 7.0, and 8.0) and assessed for transcorneal penetration in vivo in rabbit’s cornea (n=4 eyes) at three different volumes (12.5, 25, and 50 µL). Aqueous humor was aspirated through paracentesis after applying local anesthesia at 0, 5, 15, 30, 60, 120, and 240 minutes postdosing. The biosamples collected from a total of 27 groups were analyzed using liquid chromatography–tandem mass spectroscopy to determine transcorneal permeability of all four FQs individually. Results: Increase in concentration showed an increase in penetration up to 0.05%; thereafter, the effect of concentration was found to be dependent on volume of instillation as we observed a decrease in transcorneal penetration. The highest transcorneal penetration of all FQs was observed at pH 7.0 at concentration 0.05% followed by 0.025% at pH 4.5. Lastly, increasing the volume of instillation from 12.5 to 50 µL showed a significant fall in transcorneal penetration. Conclusion: The study concludes that formulation factors showed discernible effect on transcorneal permeation; therefore, due emphasis should be given on drug development and design of ophthalmic formulation. Keywords: transcorneal penetration, ophthalmic, in vivo, antibacterial